The activity of proliferation and apoptosis of thyrocytes in the thyroid tissue of patients of nodular goiter with autoimmune thyroiditis considering the polymorphism of the BCL-2 (RS17759659), CTLA-4 (RS231775), APO-1/FAS (RS2234767) genes - Sheremet, M, I.; Sydorchuk, L. P.; Shidlovskyi, V. O.; Desiateryk, V. I.; Kovalenko, A. E.; Shevchenko, S. I.; Zavgorodnyi, S. M.; Tkachuk, N. P.; Piddubna, A. A.; Завгородній, Сергій Миколайович (My University, 2020)
Nodular goiter with autoimmune thyroiditis is one of the most important problems of modern endocrinology, with inadequately studied etiological and pathogenic mechanisms of development. It is characterized by the lack of objective and reliable diagnostic methods, effective treatment methods, uncertain therapy or indications for the choice of treatment methods. A total we have examined 125 patients who were operated for a nodular endemic goiter with autoimmune thyroiditis. Investigated the activity of proliferation and apoptosis of thyrocytes in the thyroid tissue of patients of nodular goiter with autoimmune thyroiditis considering the polymorphism of the bcl-2 (rs17759659), ctla-4 (rs231775), apo-1/fas (rs2234767) genes. The expression/density markers - Fas/ FasL, Bcl-2, p53 and Ki-67 on the thyrocytes in the lymphoid infiltration and destruction areas, as well as in normal thyroid tissue (as a control) were studied. The number of immunoreactive cells, which expressed the above-mentioned regulating apoptosis and proliferation markers in NGAIT patients, depending on the genes polymorphism BCL-2 (rs17759659), CTLA-4 (rs231775) and APO-1/Fas (rs2234767) were counted. It was found that in NGAIT patients a few links of programmable thyroid cell killing of Fas-induced apoptosis were activated, and associated with the polymorphic cite of BCL-2 (rs17759659) gene and almost 6 times weaker with CTLA-4 (rs231775) gene, through enhanced expression of Fas and Fas L on the cells surface in lymphoid infiltration and destruction areas (stronger in GG genotype carriers of BCL-2 gene).
Keywords: nodular endemic goiter; autoimmune thyroiditis; apoptosis; proliferation; genes polymorphism